APLIKASI TEKNIK FINISHING MEBEL DENGAN BAHAN BERBASIS RAMAH LINGKUNGAN - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
This activity aims to: (1) introduce environmentally friendly mebele/wood finishing materials to the communities and (2) equip skill of environmentally friendly mebele/wood finishing application techniques to the communities. The  target  groups  of  this  activity  are  mebele  workers/business persons and  the  youths  in  Desa  Pathuk,  Kecamatan Pathuk,  Kabupaten Gunung Kidul, D.I. Yogyakarta. The total participants are 28 persons, 12 workers and 16 local village youths. The activity methods are: (1) lecture and  discussion, (2) question and  answer,  (3) finishing  practice,  and  (4) evaluation of the activity products. Various materials applied in the training are Ultran Aqua Politur, Aqua Lacquer Impra, Aqua  Wood Finish, and IAWF. The equipments for finishing application include various number polish papers, portable polisher, finishing material tin container, spray gun, and compressor. The products of activity are: (1) the environmentally friendly finishing  materials,  generally using  water as  a solvent  material.  (2) the procedure of environmentally friendly based finishing technique appli- cation: (a) wood surface preparation using polisher number 180, (b) rubbing wood filler evenly to the wood surface, (c) polishing by the number 240, (d) wood  stain  application  by  brushing  or  spraying,  (e)  sending  sealer application using water as solvent  material,  and  (e) final layering using alternatives of selected clear gloss/clear dove/semi gloss materials. The fifth and sixth steps, the maximum water solvent material addition of 20% for spraying application, and the maximum water addition of 10% for brushing application